Anatomy of Rouviere's Sulcus and Its Association with Complication of Laparoscopic Cholecystectomy. (24th August 2020) - Kumar, Abhijeet; Shah, Rupesh; Pandit, Narendra; Sah, Suresh Prasad; Gupta, Rakesh Kumar
Abstract : Background and Objective(s) . Rouviere's sulcus (RS) is an important anatomical landmark. The aim of this study was to find the distribution of anatomical characteristics of RS seen during laparoscopic cholecystectomy in the population of our part of the world and its association with complications. Methods . This is a prospective observational study involving patients of age ≥16 years who underwent laparoscopic cholecystectomy for uncomplicated gall stone at BPKIHS between May and July 2019. Result . 230 cases were analyzed, and RS was present in 90.4%. Open sulcus type was the commonest (54%), followed by scar type (22.9%), closed sulcus type (12.5%), and slit type (10.6%), respectively. In 59.1% of cases, it was oblique to the anterior, inferior, and external edge of the liver, while in the remaining cases, it was transverse. The mean ± SD values for operative time and duration of hospital stay in the RS visible and the RS not visible groups were 29.16 ± 8.736 and 42.9 ± 23.646 minutes, and 1.26 ± 0.440 and 1.90 ± 0.910 days, respectively (p value ≤0.001). One minor complication occurred in each group: RS initially visible group and RS visible on the adhesion release group, while 3 minor complications occurred in the RS not visible group. Only one major complication occurred in the RS not visible group. Conclusion . Identification of RS by operating surgeons is a predictor of safe laparoscopic cholecystectomy.